'Equivalence of care' in prison medicine: is equivalence of process the right measure of equity?. Issue 4 (27th September 2011) - Charles, Anna; Draper, Heather
Abstract : In recent years, the principle of equivalence has been accepted in many countries as the standard against which healthcare provision for prisoners should be measured. There are several ways in which this principle can be interpreted, but current policy in the UK and elsewhere seems to focus on the measurement and achievement of equivalence in the process of healthcare provision. We argue that it is not appropriate to apply this interpretation to all aspects of prisoner healthcare, as it does not necessarily address the challenges inherent to the prisoner population and prison setting. Consequently equivalence of health outcomes should also be considered alongside processes in the interests of providing healthcare in prison that is equivalent to that outside prison.